(untitled) (CIPEEX, 2025)
This study reflects on social responsibility, values, and human dignity, focusing on experiences of civil society initiatives dedicated to caring for human beings. Grounded in the works Mere Christianity by C. S. Lewis and The Book That Made Your World by Vishal Mangalwadi, the research investigates how Christian principles can shape social responsibility practices and foster human dignity. The methodology combines bibliographic research and analysis of social actions, particularly observing the activities of the Movimento de Cursilhos de Cristandade (MCC) in Itapaci, Goiás. Results indicate that MCC promotes human dignity through diverse initiatives such as food and clothing donations, family support, community celebrations, and marriage preparation courses, in collaboration with local parishes and communities. These actions are supported by voluntary contributions and community events, ensuring transparency and accountability. The study highlights that beyond material charity, MCC fosters moral and spiritual growth, encouraging citizens to embrace social responsibility as an expression of Christian faith. The findings reinforce that civil society organizations, guided by Christian ethics, play a vital role in strengthening social cohesion, reducing inequalities, and advancing human dignity in contemporary society.